Spatial Distribution of HIV Cases in Female Sex Workers in Palembang City (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
Key populations such as PSP (Female Sex Workers) are one of the factors that have the potential to influence the number of HIV-positive cases. The prevalence of HIV cases in Indonesia in the PSP group is 2.1%. This study aimed to examine the spatial distribution of HIV cases in PSP (Women Sex Workers) in Palembang City. This type of research is descriptive with an ecological study design. The population groups studied were 41 Public Health Center, 14 hospitals, and other HIV services such as Class I Rutan and Class IIA Women's Prisons in 18 sub-districts in Palembang City. The study used secondary data from the KT, and TIPK HIV Reports from the City Health Office, while spatial data were obtained from government websites and Google Maps. The results showed that the distribution area of ​​the PSP key population was at most 23 Ilir, Merdeka health center and Campus health center, and in the working area of ​​hospitals, detention centers, and women's prisons, there was no distribution of PSP key populations. Then, the distribution of HIV-positive cases in the PSP key population found no distribution of HIV confirmed cases in the working area of ​​the public health center or the working area of ​​hospitals, detention centers, and women's prisons. The need for further attention to policymakers on the unequal distribution of VCT services and socialization from health workers is also needed to increase awareness of PSP key populations regarding the importance of conducting VCT to prevent and control HIV cases in key populations to suppress HIV cases in Palembang City.